Zwrot postmodernistyczny albo powrót wielkich teorii w naukach społecznych - Dziamski, Grzegorz (Er(r)go. Teoria - Literatura - Kultura, 2001)
The Postmodernist Turn or the Return of Grand Theories in Social Sciences Abstract in English Grzegorz Dziamski identifies postmodernism with the rebelious spirit of the late 1960's which has been. in turn, underlain by poststructuralism (represented by Foucault, Deleuze, Derrida, Lyotard as well as Lacan and Barthes). The return of grand theories mentioned in the title refers to the impact of poststructuralism on social sciences and, more specifically, to their reorientation under the influence of poststructuralist explorations of discursive and textual practices. The essay focuses on the shift from a theoretically oriented historiography to a recognition of its inevitably narrative quality stressed by Hayden White, Frank Ankersmith or Dominick LaCapra. In social sciences, Dziamski argues, the shift implies a transition from universalistic sociological aspirations to local and particular discourses which should recognise their own limited applicability. That entails, first of all, rejecting the category of objective scientific truth which could control social development at large and, secondly, a turn to a theory which meets the requirements of specific social groups.